A Systematic Literature Review of Requirements Engineering for Self-Adaptive Systems - Sucipto, Slamet; Wahono, Romi Satria (Journal of Software Engineering, 2015)
During 2003 to 2013, the continuous effort of researchers and engineers particularly has resulted in a hugely grown body of work on engineering self-adaptive systems. Although existing studies have explored various aspects of this topic, no systematic study has been performed on categorizing and evaluating the requirement engineering for self-adaptive activities. The objective of this paper is to systematically investigate the research literature of requirements engineering for self-adaptive systems, summarize the research trends, categorize the used modeling methods and requirements engineering activities as well as the topics that most described. a systematic literature review has been conducted to answer the research questions by searching relevant studies, appraising the quality of these studies and extracting available data. From the study, a number of recommendations for future research in requirements engineering for self-adaptive systems has been derived. So that, enabling researchers and practitioners to better understand the research trends.